The Role of Customer Satisfaction in Mediating E-Service Quality, Customer Engagement on Customer Loyalty - Dina Ayu Lestari Sumiati; Rafikhein Novia Ayuanti; Agung Pambudi Mahaputra (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2026)
This study examines the influence of e-service quality and customer engagement on customer loyalty, with customer satisfaction as a mediating variable among DANA digital wallet users. Using a quantitative approach, data were collected from 150 university students in Kediri through Likert scale-based questionnaires and analyzed using SEM-PLS. The findings reveal that e-service quality and customer engagement positively and significantly affect customer satisfaction and customer loyalty. Customer satisfaction also has a significant positive effect on loyalty and successfully mediates the relationships between e-service quality, customer engagement, and customer loyalty. These results indicate that improving service quality and strengthening user engagement can enhance customer satisfaction and ultimately increase customer loyalty in digital wallet services.